A cost benefit analysis of vocational rehabilitation services provided by CRS Australia - Wills-Johnson, Nick; Kenyon, Peter; Koshy, Paul (Curtin University of Technology, 2005)
This paper analyses the costs and benefits of participation in vocational rehabilitation programs provided by CRS Australia, an Australian Government business unit . It presents estimates of cost data from CRS Australia databases and an analysis of benefits data on employment participation and the reduction in the receipt of Australian government benefits from surveys of CRS Australia clients. Non-participants who did not enter a CRS Australia program following an initial assessment interview were also examined to obtain a control group against which the outcomes from participation in CRS Australia programs can be measured.